2010
DOI: 10.1007/s10897-010-9316-y
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Perceptions, and Provider Recommendation Related to Genetic Testing for Hereditary Breast Cancer Risk among At‐Risk Hispanic Women: Similarities and Variations by Sub‐Ethnicity

Abstract: This study explored awareness of risk factors for hereditary breast and ovarian cancer (HBOC), awareness, knowledge and concerns about genetic testing, and preference for how to have genetic testing recommended by a care provider among at-risk Hispanic women. Differences in these factors among Mexican, Cuban, and Puerto Rican women were also examined. Women with a personal or family history of breast or ovarian cancer from the Tampa Bay Area participated in a qualitative interview (N=53). Data were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 60 publications
6
66
1
Order By: Relevance
“…This may explain why there is significant research investigating appropriate access to cancer genetic services by all those eligible and whether the outcomes of these services are producing favourable results such as prevention of cancer. 13,15,[25][26][27][28][29][30][31][32][33][34][35][36] It was not surprising that the majority of studies focused on the role or practice of HCPs in patients' access to genetic services. The translation of new genetic information and technology into medical care is challenged by several factors, including lack of adequate genetic workforce and increased demand of specialist care in genetics, which was also reported as a barrier in this review.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why there is significant research investigating appropriate access to cancer genetic services by all those eligible and whether the outcomes of these services are producing favourable results such as prevention of cancer. 13,15,[25][26][27][28][29][30][31][32][33][34][35][36] It was not surprising that the majority of studies focused on the role or practice of HCPs in patients' access to genetic services. The translation of new genetic information and technology into medical care is challenged by several factors, including lack of adequate genetic workforce and increased demand of specialist care in genetics, which was also reported as a barrier in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Data from both the 2000 and 2005 National Health Interview Survey suggested that less than one third of Puerto Rican women have heard of GT for inherited cancer susceptibility, compared to approximately half of all Whites (Heck et al 2008;Vadaparampil et al 2006;Wideroff et al 2003). A recent analysis of qualitative data from the larger study based in Tampa further supports this lack of familiarity with cancer-related GT as participants from various Hispanic ethnicities, including Puerto Rico, would not know how to describe GT to a friend (Vadaparampil et al 2010a). Thus, given low baseline levels of familiarity with the availability of GT for hereditary cancer, it is possible that the way the item was phrased ("I would not have GT if the test was too painful") may have led women to believe that there were other procedures beyond a blood draw for GT.…”
Section: Knowledge About Hereditary Cancer By Locationmentioning
confidence: 99%
“…Latinas, who experience many disparities in genetic counseling and testing, comprise only 1–4% of women undergoing BRCA testing [6,12,24,25]. This low participation rate suggests Latinas have low levels of awareness and knowledge about genetic counseling and testing for breast and other cancers [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Yet little research addresses gaps in US Latinas’ knowledge, attitudes and awareness of the availability of (or interest in) genetic testing for breast cancer susceptibility. Even less is known about these issues among women living along the US-Mexico border [24,26,27,3436]. …”
Section: Introductionmentioning
confidence: 99%